Urgency of Renewal of the Joint Ministerial Regulation on the Establishment of Houses of Worship: A Legal Analysis of the Status and Position - Sumilat, Juliarto (Universitas Negeri Gorontalo, 2023)
This study discusses the urgency of renewing the Joint Regulation of the Minister of Religion Number 9 of 2006 and the Minister of Home Affairs Number 8 of 2006 related to the establishment of houses of worship. Researchers in studying the problem use normative legal research methods with a statute approach related to the legal issues being handled, namely examining PBM Numbers 9 and 8 of 2006. The author intends to legally analyze the status and position of the Joint Regulations of the Minister of Religion and the Minister Domestic Affairs is from the urgency aspect of its renewal. The author also uses a conceptual approach, which is intended to analyze existing legal material so that the meaning contained in legal terms can be known. The results of the study show that the importance of renewing the Joint Regulation of the Minister of Religion No. 9 of 2006 and Minister of Home Affairs No. 8 of 2006 to create legal certainty for regulatory products; there is an excess of authority in PBM and there are multiple interpretations in the regulation of religious matters. The existence of PBM gave way to the fulfillment and implementation of worship being taken over by the regions, even though Article 10 of the Law on Regional Government states that religious affairs are an absolute authority that may not be handed over to the regions.